Ultra-wideband (UWB) antennas for breast cancer detection with microwave imaging: A review - Tale Saeidi; Sarmad Nozad Mahmood; Sahar Saleh; Nick Timmons; Ahmed Jamal Abdullah Al-Gburi; Faroq Razzaz (Results in Engineering)
In recent years, microwave imaging has attracted much attention and offers several advantages over existing imaging systems. It allows for a thorough examination of biological tissues, making it possible to identify changes in their shape and pinpoint their exact locations. One exciting development in this field is ultra-wideband (UWB) microwave imaging, which delivers superior results while using radiation that is not harmful. Antennas are a crucial part of UWB systems and require careful optimization, especially considering their proximity to the human body. Various factors need to be considered when designing antennas, including the choice of materials and dimensions, operational bandwidth, the impact of the human body on antenna performance, and the dynamics of short-pulse propagation. Recent research has focused on improving electromagnetic sensors used in these systems, whether as standalone units or as part of antenna arrays. This paper aims to comprehensively review significant advancements in high-performance UWB antenna sensors used in microwave imaging systems utilized for breast cancer detection.